Ultrasonography for nerve compression syndromes of the upper extremity - Choi, Soo-Jung (Ultrasonography, 2015)
Nerve compression syndromes commonly involve the nerves in the upper extremity. High-resolution ultrasonography (US) can satisfactorily assess these nerves and may detect the morphological changes of the nerves. US can also reveal the causes of nerve compression when structural abnormalities or space-occupying lesions are present. The most common US finding of compression neuropathy is nerve swelling proximal to the compression site. This article reviews the normal anatomic location and US appearances of the median, ulnar, and radial nerves. Common nerve compression syndromes in the upper extremity and their US findings are also reviewed.